Identifying molecular and spermatological markers to detect sperm chromatin fragmentation - KUTCHY, NASEER AHMAD; MUKHOPADHYAY, C S; BRAH, G S; ARORA, J S (The Indian Journal of Animal Sciences, 2014)
Transition nuclear proteins (TNPs) are the primary basic proteins produced from the histone replacement. Protamines (PRMs) and transition nuclear proteins are important for maintaining the sperm chromatin integrity, resistance to cryopreservational damage, potentiating fertilizing ability of sperm, preventing embryo deaths and abortions. Hence this histone to protamine replacement should be highly conserved among the males of different species. In the present study, blood and semen samples from 43 cattle and 17 buffalo bulls were collected to isolate genomic DNA and to study sperm chromatin fragmentation following varying period of cryopreservation. Single stranded conformational polymorphism (SSCP) was done to detect any single nucleotide polymorphisms (SNPs) in the coding exonic regions of TNP 1 and 2 as well as PRM 1 and 2 genes. The SSCP analysis did not reveal any SNP in these genes. This may be due to conserved pattern of these genes. The sperm chromatin fragmentation determined by comet assay was significantly different between the acceptable semen donating cattle as well as the buffalo bulls.